Developing Companionship with the Left-Behinds: University Social Responsibility and a Collaborative Approach to Rural Regeneration in the Badlands Region of Taiwan (Transactions of the Association of European Schools of Planning, 2022)
The subject of regional inequality has been garnering the attention of scholars over the past decade and has generated debates on territories forgotten by mainstream economic activities. Left-behind places are a global phenomenon yet with various situated conditions in different development contexts that required customized, place-based solutions. This paper discusses a possible approach to work with the left-behinds: using the university as an institutional resource to engage people and places in regional regeneration. Using the [anonymised] project as an example, we describe the learning journey of developing the ground solutions and companionship between a research university and left-behind communities in the rural badlands region. Adopting a hybrid of an asset-based approach to community development and collaborative planning for regional development, this case demonstrates a potential level-up strategy for sustainable development for the lagging region.
Keywords: Left-behind; university social responsibility; place-based; asset-based; collaborative planning